2020
DOI: 10.3390/ijerph17103711
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Links between Polychronicity and Job Performance from the Person–Environment Fit Perspective—The Mediating Role of Well-Being

Abstract: Polychronicity refers to the preference of some individuals to structure their time in order to deal with multiple tasks simultaneously in a short period of time. Past research regarding the correlation between individual polychronicity and performance presented distinct arguments. Although most studies supported a positive correlation with performance, empirical findings showed inconsistent results, indicating the presence of other influencing factors. According to the person–environment fit theory and self-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Chebat and Michon [16]; Wu et al [17]; Ying et al [18] Product display, scent, lighting, music, a pleasant mood, and environment Experience with staff service Young et al [19]; Dabholkar and Abston [20] All contact with staff/authentic moments and tangible and intangible service factors…”
Section: Experience With Shopping Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Chebat and Michon [16]; Wu et al [17]; Ying et al [18] Product display, scent, lighting, music, a pleasant mood, and environment Experience with staff service Young et al [19]; Dabholkar and Abston [20] All contact with staff/authentic moments and tangible and intangible service factors…”
Section: Experience With Shopping Environmentmentioning
confidence: 99%
“…In the context of retail, Judd [30] indicated that staff members are obliged to create value for and deliver quality service to customers. Wu et al [17] held that service quality affects customer satisfaction through various factors. Ying et al [18] stated that service quality is a critical driver affecting customer satisfaction.…”
Section: Customer Experience With Staff Service and Customer Satisfacmentioning
confidence: 99%
“…Well-being is also called job satisfaction, where individuals consider their work process, content, and situation to agree with their intrinsic perceptions. Wu et al [ 21 ] defined well-being as the degree that an individual and/or the majority of employees perceive(s) the well-being of their work, where the degree of well-being is related to salary, raises, work location, work time, type of work, promotion opportunities, interpersonal relationships, and management. Ilies et al [ 22 ] suggested that well-being is determined by employees’ perceived work devotion and rewards, as employees compare their results with those of other members in the same organization; a more equal result will yield stronger feelings of well-being.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…To reduce potential confounding effects, several variables commonly thought to correlate with job-related wellbeing were controlled for both steps of the study. The personal characteristics were measured by a region variable (0 = rural, 1 = urban) [ 22 ], a gender variable (0 = female, 1 = male) [ 22 , 25 ], an age group variable (1 = 20 or below, 2 = 21–30, 3 = 31–40, 4 = above 40) [ 22 ], marital status (0 = unmarried, 1 = married) [ 22 ], education (1 = college or below, 2 = bachelor, 3 = master, 4 = doctor) [ 3 , 23 ], working hours per week (1 = 20 h or below, 2 = 21–40 h, 3 = 41–60 h, 4 = 61–80 h, 5 = above 80 h) [ 3 , 24 , 29 ], annual income (1 = RMB 10,000 or below, 2 = RMB 10,001–50,000, 3 = RMB 50,001–100,000, 4 = RMB 100,001–150,000, 5 = RMB 150,000 or above) [ 22 , 25 , 29 ], and industry variables which are consist of 9 type of industries, including civil service(reference group in the first step), farming/mining(0 = no, 1 = yes), manufacturing(dummy variable 0 = no, 1 = yes in the first step, reference group in the second step), power supply/construction/geological exploration/hydraulic management(0 = no, 1 = yes), transportation and network(0 = no, 1 = yes), whole/retail/restaurant(0 = no, 1 = yes), real state/finance(0 = no, 1 = yes), science/education/arts/health/media/social service(0 = no, 1 = yes), and others(0 = no, 1 = yes) [ 23 , 24 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to Atienza et al [ 16 ], job control or autonomy indicates a stronger association with intrinsic job satisfaction. Employee-owned companies report higher levels of job satisfaction, which may be derived from a greater sense of autonomy among the employees [ 29 , 30 ]. Bianchi [ 13 ] compares the utilities of employees and entrepreneurs and finds that the non-pecuniary dimensions of job satisfaction, particularly autonomy, have an effect on the difference in utility between the two groups.…”
Section: Introductionmentioning
confidence: 99%